Synthesis and Biological Screening of Substituted 2-Aminocyano Pyridines - DRABU, SUSHMA; KUMAR, NITIN (Asian Journal of Chemistry, 2010)
A variety of novel 2-aminocyano pyridines were prepared by reacting different chalcones with malonitrile. All the newly synthesized compounds were characterized by spectral analysis (1H NMR and IR spectra). Newly synthesized compounds were screened for their antiinflammatory and antibacterial activity.